The Contribution of Working Memory Capacity in Developing the Learner’s Oral Proficiency Case Study: Third and Fourth Year Students, Ecole Normale Supérieure of Constantine - KHERIBET, Souheila (Journal of Human Sciences, 2017)
This study is an attempt to highlight the role working memory capacity plays in developing language learners’ oral proficiency. It also targets the issue of identifying the very essential component of the same system, the phonological loop, in the speech production process. This article begins with a literature review explaining the different parts of the human memory as a whole, and the major constituents of working memory in particular. This is followed by an experimental study analysis conducted on a population of 45 students in the Department of English in the Teacher Training School of Constantine, and the results of which revealed that the specific characteristics and functions of working memory would be of great significance in improving learners’ speaking fluency, thus, confirming and validating our hypothesis.